Wildlife Conservation and Eco-development Programme - a Case Study - Singh, R. L. (Indian Forester, 1991)
Conservation of wildlife is an essential activity for the future progress of a country. India has established an extensive network of Protected Areas of 74 National Parks, 411 Wildlife Sanctuaries and 18 Tiger Reserves, extending to 4.18% of its geographical area. The preservation of the Protected Areas, depends upon the proper management of the buffer areas, which are primarily for meeting the forest-based needs of the people, living around the core areas. The study of the eco-development programme launched in Ranthambhore Tiger Reserve Indicates that there are ways to integrate the interests of the wildlife and local people but there is no way to preserve wildlife without integrating the interests of local people.